Nine Steps to Memorize the Quran Using the At-Taisir Method At Pondok Taajul Huffazh - Samsurizal, Samsurizal; Uminisara, Uminisara; Husna, Aisyah Rahmatul; Islamia, Zelfi; Mutiah, Syarifah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2020)
Choosing the right method for memorizing the Quran can help make memorizing the Quran easier. The author found a Quran hut that uses the At-Taisir method for memorizing. This method was pioneered by Ustadz Adi Hidayat. This research aims to analyze how to memorize the Quran using the At-Taisir method. The research method used is a qualitative method with a case study approach. Overall, the research results show nine steps in memorizing the Quran using the At-Taisir method. the nine steps are i) starting the memorization activity by praying ii) repeating the previous memorization iii) remembering the meaning of each word in a verse of the Quran iv) understanding the meaning of the translation of sentences in a verse of the Quran v) take turns viii) the teacher tests the students' memorization of one page of the Quran. ix) evaluate the memorization for one week by testing the accuracy of the attachment. The results of this research can be used as initial data for subsequent researchers in studying different issues related to this problem as well as various other issues that are relevant to this context.